Interface behaviour of the composite stabilised earth blocks (SEB) - date palm fibre in earthen structures - Mahi, Abdelhak; Fouchal, Fazia; Hamouine, Abdelmadjid; Abbes, Boussad (European Journal of Environmental and Civil Engineering, 2026)
The growing demand for construction presents a critical challenge, particularly considering the depletion of non-renewable resources. Consequently, the use of locally available materials is essential for future construction practices. This study presents experimental and numerical investigations into the interaction between date palm fibres and stabilised earth blocks (SEBs). SEBs were stabilised using white cement, lime, and a white cement–lime mixture. A pull-out test, adapted specifically for earthen materials, was developed and conducted on single fibres embedded in different SEBs. The results demonstrate the effectiveness of this method in evaluating the interface behaviour of SEBs reinforced with vegetable fibres. The use of untreated fibres revealed that SEBs stabilised with white cement exhibited a 16% increase in pull-out load compared to unstabilised earth. Autoclave treatment of the fibres significantly enhanced adhesion at the fibre–earth interface, particularly in SEBs stabilised with white cement, resulting in a pull-out load over 230% higher than that of unstabilised earth. However, the presence of moisture was found to adversely affect the behaviour at the fibre–matrix interface. A three-dimensional finite element model of the pull-out test was also developed, showing good agreement with experimental results and successfully reproducing the observed behaviour.
_eprint: https://doi.org/10.1080/19648189.2025.2584116
Keywords: Stabilised earth blocks; adhesion; date palm fibres; durability; interface; pull-out test; modelling and finite element simulation